Interaural asymmetry of dynamic range: Abnormal fusion, bilateral interference, and shifts in attention - Anderson, Sean R.; Gallun, Frederick J.; Litovsky, Ruth Y. (Frontiers in Neuroscience, 2023)
Speech information in the better ear interferes with the poorer ear in patients with bilateral cochlear implants (BiCIs) who have large asymmetries in speech intelligibility between ears. The goal of the present study was to assess how each ear impacts, and whether one dominates, speech perception using simulated CI processing in older and younger normal-hearing (ONH and YNH) listeners. Dynamic range (DR) was manipulated symmetrically or asymmetrically across spectral bands in a vocoder. We hypothesized that if abnormal integration of speech information occurs with asymmetrical speech understanding, listeners would demonstrate an atypical preference in accuracy when reporting speech presented to the better ear and fusion of speech between the ears (i.e., an increased number of one-word responses when two words were presented). Results from three speech conditions showed that: (1) When the same word was presented to both ears, speech identification accuracy decreased if one or both ears decreased in DR, but listeners usually reported hearing one word. (2) When two words with different vowels were presented to both ears, speech identification accuracy and percentage of two-word responses decreased consistently as DR decreased in one or both ears. (3) When two rhyming words (e.g., bed and led) previously shown to phonologically fuse between ears (e.g., bled) were presented, listeners instead demonstrated interference as DR decreased. The word responded in (2) and (3) came from the right (symmetric) or better (asymmetric) ear, especially in (3) and for ONH listeners in (2). These results suggest that the ear with poorer dynamic range is downweighted by the auditory system, resulting in abnormal fusion and interference, especially for older listeners.